A node positioning method for IoT based on LSSVR and optimized particle swarm algorithm. Issue 3 (17th February 2022) - Zhang, Yang; Zhao, Kaixin; Ren, Gang; Zhu, Mingdong
Abstract : Aiming at the problem that the optimal parameters of the least square support vector regression (LSSVR) localization model in Internet of Things (IoT) are difficult to determine, a positioning method based on the improved particle swarm optimization (PSO) algorithm is proposed. First, the positioning model is constructed by LSSVR, then the PSO algorithm is improved by adaptively adjusting the inertia weights and the learning factors, and finally the improved PSO algorithm is used to search the optimal parameters of the LSSVR positioning model, which avoids the blindness of the parameter search. The simulation results show that the positioning accuracy of the proposed algorithm is improved by 25.9% and 19.7%, respectively, compared with the LSSVR and PSO‐LSSVR algorithms, and has better positioning stability and real‐time performance. Abstract : Based on the improved PSO algorithm and LSSVR localization model, a node localization algorithm is proposed with better performance than the benchmark. The algorithm has the potential to be applied in mobile node localization.